(untitled) (Palíndromo, 2025)
The text interweaves the author’s personal experience with the Monstera plant (commonly known as the Swiss Cheese Plant) with Donna Haraway’s concept of "making kin," searching to think about the interdependence between humans and other species.The author describes the process of creating her musical album "Monstera," using the plant as a starting point for sonic experimentation. This process goes beyond a literal translation between plant and subject, trought "a language of the sensible." The author seeks to rethink an anthropocentric worldview, establishing a horizontal relationship of care with other life forms. The text presents itself as an autobiographical account interwoven with discussions of contemporary theories about the Anthropocene and the role of art in constructing new ways of thinking and acting in the world. Through her musical experience and her relationship with the plant, the author invites us to reconsider our relationship with the natural world and seek new forms of coexistence.